Effects of Educational Intervention on Self Esteem among Burn patients - Sobia Zahra, Zunaira Aziz, Kabir Ozigiabdullahi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Burns are a potentially fatal illness as well as a serious traumatic event with a high risk of complications. Burn victims must also adjust to their new body image. Burn patients face numerous challenges. Patients recovering from severe burns may experience extreme distress, with devastating physical and psychological consequences. Aim: To investigate the effect of educational intervention on self-esteem among burn patients Method: A quasi experimental study conducted in Pak-Italian Modern Burn Center Multan over 108 burn patients: Data were collected through Rosenberg’s global self-esteem scale. Data was analyzed through Chi Square and paired t test with a significance of p<0.05; However data display in the form of frequency table. Result: The majority of the patients (60.2%) were male aged 32 to 45, lived in cities (52.8%) and half of the patients (48.1%) were single on marital status. Patients had low self-esteem prior to the intervention, with a mean score of 16.21±4.41 before intervention, and 30.72±4.49 after intervention, with a significance of P equal to 0.002. Practical Implication: Educational interventions and support systems help to enhance the psychological well-being and overall quality of life for burn patients and facilitating their journey towards physical and emotional recovery. Conclusion: The current study found that providing educational intervention at the burn unit was effective when it came to educating patients to promote coping with changes, strengthening ability and enhancing self-esteem, using relaxation techniques, providing mental health, and sexual relations. Encouraged patients to be active participants in their care, which resulted in significant improvements in burn patient’sself-esteem. Keyword: Educational intervention, self-care management, self-esteem, Burn patients